2019
DOI: 10.1101/555847
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep behavioural phenotyping reveals divergent trajectories of ageing and quantifies health state inC. elegans

Abstract: Neurodegenerative diseases may be the cause or the consequence of an acceleration of physiological ageing. Evidence for this concept is lacking due to practical limitations of human studies. Here, we compared the processes of physiological and pathological ageing of individual C. elegans over their lifespan. Using multi-parametric phenotyping, trajectories of ageing can be defined within a phenotypic landscape made of a large set of phenotypical features. Rather than an acceleration of ageing, a model for synu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Qualitatively, the short- and long-lived wild type animals followed similar phenotypic trajectories in the subspaces we selected. Using the same methodology, we previously observed that different genotypes can follow distinct trajectories [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Qualitatively, the short- and long-lived wild type animals followed similar phenotypic trajectories in the subspaces we selected. Using the same methodology, we previously observed that different genotypes can follow distinct trajectories [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health state and longevity are affected by genetics and environment. We previously observed different phenotypic trajectories of ageing for two different genotypes (Martineau et al, 2019). However even isogenic worms ageing in a controlled environment show wide inter-individual differences in lifespan.…”
Section: Discussionmentioning
confidence: 97%
“…It is calculated as the mean difference between the maximum value (90 th percentile) and minimum value (10 th percentile) for each feature and should be an indicator of the phenotypic flexibility of the animals. This index is applicable to physiological as well as pathological ageing (Martineau et al, 2019). Our health index varies along life and appeared highly dependent on lifespan.…”
Section: Long-lived Animals Have a Better Healthmentioning
confidence: 99%
“…Martineau (23,32) Proteome ratios over time (numerical) Narayan (20) Gene expression over time (numerical) Hastings (21) Gene expression over time (numerical) Bgee (33) Gene effect on lifespan (categorical) GenAge (6,34) Protein Phosphorylation (numerical) Huang (24) Pathway labels (categorical) Uniprot (35) Interacting genes (categorical) Wormbase (29) Disease information (categorical) Wormbase (29) Human ortholog (categorical) Wormbase (29) Gene description (categorical) Wormbase ( 29)…”
Section: Data Collection and Formattingmentioning
confidence: 99%
“…A further benefit of working with C. elegans is the vast range of available data including time-based transcriptomic, proteomic, phosphorylation status, molecular data and detailed morphological data, allowing to describe the relationships between different Omics layers and their possible contributions to the aging process (20,21,23,24). However, prioritization of aging-related targets remains a challenge in this organism due to the many existing targets and their association with longevity and not necessarily the aging process.…”
Section: Introductionmentioning
confidence: 99%